2018
DOI: 10.1139/apnm-2017-0533
|View full text |Cite|
|
Sign up to set email alerts
|

A multi-ingredient nutritional supplement enhances exercise training-related reductions in markers of systemic inflammation in healthy older men

Abstract: more authors) (2018) A multi-ingredient nutritional supplement enhances exercise training-related reductions in markers of systemic inflammation in healthy older men. Applied Physiology, Nutrition and Metabolism, 43 (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
2
14
0
2
Order By: Relevance
“…The same logic applies to MIS vs. single-nutrient supplementation as the former theoretically stimulates several processes simultaneously, thus 'circumventing' the main limitation of using nutritional monotherapies, such as whey or BCAAs, e.g., anabolic resistance with aging. Common nutrients with documented SM benefits in MIS include whey [53,69,70], vitamin D [53,61,62,69,70], polyunsaturated fatty acids (n-3 PUFAs; EPA and DHA [53,63,64,69,70]), and creatine [53,[65][66][67][68][69][70]. As previously demonstrated by Bell et al, this blend of nutrients may be safely combined to potentiate SM growth independently or in conjunction with supervised RE/HIIT [53].…”
Section: Discussionmentioning
confidence: 89%
“…The same logic applies to MIS vs. single-nutrient supplementation as the former theoretically stimulates several processes simultaneously, thus 'circumventing' the main limitation of using nutritional monotherapies, such as whey or BCAAs, e.g., anabolic resistance with aging. Common nutrients with documented SM benefits in MIS include whey [53,69,70], vitamin D [53,61,62,69,70], polyunsaturated fatty acids (n-3 PUFAs; EPA and DHA [53,63,64,69,70]), and creatine [53,[65][66][67][68][69][70]. As previously demonstrated by Bell et al, this blend of nutrients may be safely combined to potentiate SM growth independently or in conjunction with supervised RE/HIIT [53].…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, evidence has emerged to demonstrate that a MIS compromising of WP (30 g), creatine (2.5 g), vitamin D (500 IU), calcium (400 mg) and n-3 FAs (1500 mg) may have a beneficial effect on skeletal muscle mass and strength [208,211], inflammation [212] and cognition [213] in older adults, although no effect on exercise-induced myogenesis was observed [214]. MIS, however, did not benefit the adaptive remodelling response to a 12-week multi-modal, concurrent RET and high-intensity interval training intervention in older men [215].…”
Section: Multi-ingredient Supplementsmentioning
confidence: 99%
“…Among 84 postmenopausal women, a multicenter 18-month supplementation trial reported a protective effect of WP on markers of inflammation, in comparison to a maltodextrin supplementation [113]. A multi-ingredient nutritional supplement was effective in progressively reducing the plasma level of TNF-α and IL-6 among healthy older men, in a two phase study with 6 weeks of supplementation alone, followed by 12 weeks of supplementation with physical exercise [114]. The multi ingredient supplement provided contained 30 g WP, 2.5 g creatine, 400 mg calcium, 500 IU vitamin D, and 1500 mg n-3 PUFA.…”
Section: Inflammation Markers (Seven Studies)mentioning
confidence: 99%